Analysis of eVTOL multicopter weight and power budget as a function of the number of rotors - Usov, D.; Filippone, A.; Bojdo, N. (My University, 2021)
In this work, we focused on predicting the power budget and weight variation of an electric, wingless multicopter operating in a typical UAM mission as a function of the total number of rotors in the propulsion group. The aerodynamic performance was obtained using the actuator disk inflow model, and weights were estimated based on semi-empirical scaling laws of the electrical components in the power train. The key aspect of this analysis procedure is that it accounted for the potential failure events that reflected on the power budget and weight of the rotorcraft. Results describe the weights of the propulsion system components, power requirements, and energy budget of the rotorcraft as a function of the total number of rotors. The main conclusion is that a larger number of rotors is beneficial for the rotorcraft’s weight and power budget, for a number of rotors within the practical range, i.e. ???? ? [6, 20]. A global minimum exists for both energy budget requirements and MTOW if the efficiency of the power train degrades with an increasing number of rotors. Optimising multicopter for minimum weight can be misleading as it does not result in the most efficient configuration energy budget-wise.